Analysis of Scaffolding Safety in Construction Site and Preventive Actions for Implementation of Safety - B, Hagaensh; N, Balasundaram (International Journal of Psychosocial Rehabilitation, 2020)
The economy Construction industry is the second largest revenue generating industry next to agriculture in India, Most of the construction sites lack safety in construction One of several risky workstations includes the building sites. They consist of most risky works like lifting material, scaffolding for working at heights. Major cause of accidents at these sites for any workforces is doing hazardous jobs. Most of the accidents are happening because of unsafe acts and falling from heights at construction work places. Construction industry depends on massive labour forces in India and this industry seldom follows the safety policies laid by the government. The workforces do not know the dangers of construction sites since safety procedures are not followed properly and observed constantly. Accidents and incidents and injuries are high since the awareness of risk involved is not known by the employees. Rules and regulations of safety are not trained well and followed. In this paper a survey is taken on the management of safety in construction industries. Questionnaire is framed for industries to cover different levels of workforces. This study is concentrated specifically the issues related to scaffolding. Outcomes of the questionnaire surveys are worked for four different construction sites. Safety was educated to workforces through training programmes related to scaffolding. Understanding ability of the workers were collected previously and subsequently at the end of the program of training and outcomes got were exposed to statistical analysis to the learning program.